A deep dive into hyperbaric environments and intraocular pressure—a systematic review - Lentz, Paul Connor; Lim, Sheng Yang; Betzler, Bjorn Kaijun; Miller, Darby D.; Dorairaj, Syril K.; Ang, Bryan Chin Hou (Frontiers in Medicine, 2024)
Purpose: SCUBA diving exposes participants to a unique hyperbaric environment, but few studies have examined the effects of such an environment on intraocular pressure (IOP) and glaucoma. This systematic review aims to consolidate recent literature findings regarding the impact of increased atmospheric pressure on IOP and glaucoma.Methods: Three online databases were searched to identify publications encompassing the subjects of diving or increased atmospheric pressure in conjunction with IOP or glaucoma.Three reviewers independently screened the publications and identified eligible articles.Relevant data was extracted from each article. The heterogeneity of the data precluded the conduct of a meta-analysis.Results: Nine studies met the inclusion criteria. Six experimental studies employed hyperbaric chambers to measure IOP under simulated diving conditions. Among these, IOP exhibited a reduction with increased atmospheric pressures in four studies, while the findings of two studies were inconclusive. One study measured IOP pre-and post-dive and another measured IOP with and without a diving mask. Post-dive, a decrease in IOP was observed, and a statistically significant reduction was noted when subjects wore a diving mask. A retrospective study examining the incidence of acute angle closure glaucoma attack found no association with weather or atmospheric pressure.The majority of studies found IOP to decrease with increased atmospheric pressure and after diving. The mechanisms underlying this reduction remain incompletely understood, with potential contributors including changes in ocular blood flow, sympathetic responses, and increased oxygenation. Hyperbaric chambers may have potential in future glaucoma treatments, but more studies are required to draw reliable conclusions regarding the safety of diving for glaucoma patients.